PERBEDAAN KOMBINASI FENTANYL DAN DEXAMETHASONE DIBANDINGKAN FENTANYL TUNGGAL DALAM MENCEGAH SHIVERING PASCA ANESTESI SPINAL PADA SEKSIO SESARIA EMERGENCY - Asri; Cemy Nur Fitria; Pandu Aseta; Sulastri (JOMIS (Journal of Midwifery Science), 2026)
Background: Shivering is a common complication following spinal anesthesia during cesarean section, with an incidence of 40-60%. In emergency cesarean section cases, this risk is higher due to patients presenting with labor exhaustion, hemodynamic disturbances, and acute stress responses. Preliminary data from RSUD Arifin Achmad, Riau Province, for November-December 2025 recorded approximately 32 emergency cesarean section cases, with several patients experiencing post-spinal anesthesia shivering. Intrathecal fentanyl has been used to prevent shivering; however, the addition of dexamethasone as an anti-inflammatory adjuvant is expected to provide a more optimal protective effect. Objective: To compare the effectiveness of fentanyl combined with dexamethasone versus fentanyl alone in preventing the incidence and severity of post-spinal anesthesia shivering in emergency cesarean section patients. Methods: A quantitative comparative study using a quasi-experimental post-test only control group design. A total of 24 patients were divided into two groups: Group 1 (Fentanyl + Dexamethasone, n=12) and Group 2 (Fentanyl alone, n=12). Shivering severity was assessed using the Wrench Scale and analyzed with the Mann-Whitney test. Results: The incidence of shivering in Group 1 was 8.3% compared with 33.3% in Group 2. The mean Wrench Scale score in Group 1 was lower (0.33 +/- 0.78) than in Group 2 (0.83 +/- 1.11). Mann-Whitney analysis showed p = 0.193 (p > 0.05), no statistically significant difference. Conclusion: The combination of fentanyl and dexamethasone demonstrated a better clinical trend in reducing the incidence and severity of post-spinal anesthesia shivering in emergency cesarean section compared with fentanyl alone, although statistical significance was not reached, possibly due to the small sample size